Management of the Influence of Organized Interests on Public Policy - Gumuliauskienė, Anželika (Socialiniai tyrimai, 2021)
The article analyzes the management of the influence of organized interests on public policy. The article reveals the concept of organized interests, the essential differences in comparing the concepts of organized interests and interest groups. The article takes the view that organized interests are a more neutral concept that better explains the nature of all actors seeking to influence public policy-making. The author of the article is of the opinion that the concept of interest groups – due to the disagreement of scientists in defining it – causes a lot of confusion when comparing the results of different researches and using the theoretical insights of other scientists. Organized interests interact with other public policy makers to influence policy outcomes. This article analyzes the ways in which organized interests can influence public policy. According to the author of the article, by identifying the ways of influencing public policy, it is possible to envisage ways to manage that influence. The article applies methods of analysis, synthesis, generalization and comparative analysis of scientific literature.
Keywords: organized interests; interest groups; influence of organized interests; influence management